Chlorpromazine Sensitizes Progestin-Resistant Endometrial Cancer Cells to MPA by Upregulating PRB - Cui, Yunxia; Wu, Huiwen; Yang, Linlin; Huang, Ting; Li, Jian; Gong, Xiaodi; Li, Lijuan; Sun, Xiao; Mao, Fei; Wang, Yudong (Frontiers in Oncology, 2021)
Medroxyprogesterone acetate (MPA) is the main conservative treatment for endometrial cancer (EC) patients desirable to preserve fertility and those who cannot suffer from surgery. Considering the high incidence of progestin resistance and recurrence of MPA treatment, we reproposed antipsychotics chlorpromazine (CPZ) as a new strategy for both progestin-sensitive and -resistant endometrial cancer. Cytobiology experiments indicated that CPZ could significantly suppress proliferation, migration/invasion and induce apoptosis in Ishikawa (ISK) and KLE EC cell lines. And xenograft mouse models were constructed to validate the antitumor effect and toxicity of CPZ in-vivo. CPZ inhibited the growth at a low dose of 3mg/kg and the mice exhibited no signs of toxicity. Next, concomitant treatment and sequential treatment with CPZ and MPA were proceeded to analysis the synergistic effect in EC cells. Concomitant treatment only performed a limited synergistic effect on apoptosis in ISK and KLE cells. Nevertheless, sequential treatment showed favorable synergistic effects in progestin-resistant KLE cells. Finally, a stable MPA-resistant cell line shRNA was established to explore the mechanism of CPZ reversing progestin resistance. Immunoblot data showed that CPZ inhibited the activation of PI3K/AKT signal in ISK and KLE cells and upregulated PRB expression in progestin-resistant cells, by which CPZ overcame progestin resistance to MPA. Thus, CPZ might act as a candidate drug for conservative treatment and sequential treatment with CPZ and MPA could be a suitable therapeutic option for progestin resistant patients.